Correlation of Vitamin D and Antimullerian Hormone Level in Infertile Women with Polycystic Ovary Syndrome and Obesity - Usman, Fatimah; Saleh, Irsan; Effendi, Kms. Yusuf; Putra, Hadrians Kesuma; Abadi, Adnan; Siahaan, Salmon Charles Pardomuan Tua; Kesty, Cindy; Rizda, Dian Permata; Stevanny, Bella; Lestari, Peby Maulina (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Increasing amount of research indicates that women with PCOS are more likely to have a shortage in vitamin D with abnormally high anti-Müllerian hormone (AMH) levels. This study aims to assess the correlation between vitamin D and Anti-Mullerian Hormone (AMH) levels in infertile women with polycystic ovarian syndrome (PCOS) and obesity. Method: This observational cross-sectional study examined all obese women with PCOS who sought infertility treatment at Dr. Mohammad Hoesin Hospital Palembang from August 2021 to November 2021. PCOS diagnosis was determined using the Rotterdam criteria. All research subjects underwent a physical examination and transvaginal ultrasound to evaluate body mass index (BMI) and polycystic ovary morphology. Blood samples were collected to evaluate their testosterone, AMH, and vitamin D levels. Statistical analysis was performed using the Spearman correlation test with IBM® SPSS Statistics version 24. Results: Thirty infertile women with PCOS and obesity were included in the study, with average age of 31.17±4.48 years and average BMI of 33.45±2.67 kg/m2. The majority of the subjects had polycystic ovary morphology (86.7%) and oligomenorrhea (76.7%). No correlation between BMI and vitamin D as well as AMH levels was found in infertile women with PCOS and obesity. The Spearman test showed moderate negative correlation (p = 0.011. r = -0.458) between vitamin D and AMH levels in infertile women with PCOS and obesity. Conclusion: There is a moderate negative correlation between vitamin D and AMH levels among infertile women with PCOS and obesity. Further research is required to comprehend the role of vitamin D in female fertility.Korelasi Vitamin D dan Kadar Hormon Anti-Müllerian pada Wanita Infertil dengan Sindrom Ovarium Polikistik dan ObesitasAbstrakPendahuluan: Semakin banyak penelitian melaporkan bahwa wanita dengan PCOS cenderung mengalami defisiensi vitamin D dengan penignkatan kadar hormon anti-Müllerian (AMH). Penelitian ini bertujuan untuk mengkaji hubungan vitamin D dan kadar AMH pada wanita infertil dengan sindrom ovarium polikistik (SOPK) dan obesitas.Metode: Penelitian ini merupakan studi observasional potong lintang terhadap seluruh wanita infertil dengan SPOK dan obesitas yang di RSUP Dr. Mohammad Hoesin Palembang pada bulan Agustus 2021 hingga November 2021. Diagnosis SOPK ditegakkan berdasarkan kriteria Rotterdam. Seluruh subjek penelitian menjalani pemeriksaan fisik dan ultrasonografi transvaginal untuk menilai indeks massa tubuh (IMT) dan morfologi ovarium polikistik. Sampel darah dikumpulkan dari semua wanita untuk mengukur kadar testosteron, AMH, dan vitamin D. Analisis statistik dilakukan dengan menggunakan uji korelasi Spearman menggunakan IBM® SPSS Statistics versi 24.Hasil: Tiga puluh wanita infertil dengan SOPK dan obesitas dilibatkan dalam penelitian ini dengan usia rata-rata 31,17±4,48 tahun dan rata-rata IMT 33,45±2,67 kg/m2. Mayoritas subjek memiliki morfologi ovarium polikistik (86,7%) dan oligomenore (76,7%). Tidak ada korelasi antara IMT dan vitamin D maupun kadar AMH pada wanita infertil dengan SOPK dan obesitas. Uji Spearman menunjukkan korelasi negatif sedang (p=0.011.r=-0.458) antara kadar vitamin D dan AMH pada wanita infertil dengan SOPK dan obesitas. Kesimpulan: Kadar vitamin D berkorelasi negatif dengan kadar AMH pada wanita infertil dengan SOPK dan obesitas. Penelitian lebih lanjut diperlukan untuk memahami peran vitamin D pada kesuburan wanita.Kata kunci: Anti-Müllerian Hormone, Indeks Massa Tubuh, Obesitas, Sindrom Ovarium Polikistik, Vitamin D